In situ spectroscopic and electrochemical impedance study of gold/poly (anthranilic acid) core/shell nanoparticles. (May 2015) - Golshaei, Rana; Guler, Zeliha; Ünsal, Cem; Sarac, A. Sezai
Graphical abstract: Highlights: We report a facile method to prepare (gold/poly anthranilic acid) core/shell nanostructures. In situ UV–Vis spectroscopy of synthesized Au/PANA nanocomposites is investigated. Electroactivity of Au/PANA core/shells are studied by electrochemical impedance spectroscopy (EIS). Equivalent circuit modeling of Au/PANA nanocomposites is performed. Au/PANA nanocomposites capacitances were determined by the change of ratio and amount of Au/PANA. Abstract: The present study reports a facile and simple method to prepare (Gold/Poly Anthranilic acid) (Au/PANA) core/shell nanostructures with uniform size and morphology in an aqueous solution through oxidation of the monomer (3-aminobenzoic acid) and reduction of the Au(III) ions simultaneously. In this work, gold nanoparticles were highly dispersed and stabilized by the oxidation of 3-aminobenzoic acid in order to form a uniform metal–polymer core/shell nanocomposite. Fabricated nanocomposites have been characterized by UV–Visible spectroscopy, attenuated total reflection–Fourier transform infrared (ATR–FTIR) and X-ray diffraction. Morphology of nanocomposites was analyzed by atomic force microscopy (AFM), scanning electron microscopy (SEM). Electroactivity of Au/PANA core/shells were investigated by electrochemical impedance spectroscopy (EIS) and equivalent circuit modeling was performed. In situ spectroscopic characterization of polymerization reaction indicated the reaction between gold ions and 3-aminobenzoic acid and formation of Au/PANA core/shell nanoparticles during reaction period. FTIR–ATR and UV–Vis spectroscopy results evidenced the incorporation of Au nanoparticles into PANA. XRD analyses indicated the high degree of crystallinity of Au. SEM images showed homogeneous distribution of Au/PANA core/shell nanocomposites with the size of ∼20 nm. EIS data suggested that as the initial concentrations of Au and PANA increased, the core/shell nanocomposites started to act like as an ideal capacitor.